Kajian Semiotika pada Road Sing Restoran Taman Pringsewu Yogyakarta - Dyah Nurhayati (Institut Seni Indonesia Yogyakarta, 2010)
The Semiotics of Road Sign in Taman Pringsewu Restaurant. This study aims at revealing the meaning of road signs as the elements of the sign system of the Pringsewu restaurant in Yogyakarta. The samples that are taken based on the message (its competitive advantage) include the ‘free formalin’ sign, the ‘alert chicken carcass’ sign, the ‘free hotspots’ sign, and the ‘playback’ sign. The four signs are important because they involve public interest issues and trends that represent the whole road signs. This study operates a qualitative method with a semiotic theory-based explanation. The data gathered are analyzed in a qualitative-interpretative way. It relates to the principles of visual communication design. The result of this study confirms that road signs carry the public needs issues and modern lifestyles. Keywords: Pringsewu, road signs, meaning signs